(untitled) (SCIENCE TIME JOURNAL, 2026)
This study examines the linguocognitive representation of the concept of friendship in English and Uzbek languages. Friendship is considered a universal cultural and social phenomenon reflecting interpersonal relations and moral values within linguistic communities. The research aims to identify the cognitive and linguistic mechanisms through which the concept of friendship is expressed in both languages and to reveal similarities and differences in their conceptual structures. The study applies comparative, conceptual, and linguocognitive analysis methods. Linguistic units such as proverbs, phraseological expressions, and lexical items are analyzed. The findings show that in both languages friendship is associated with loyalty, trust, emotional support, and mutual assistance.